A COMPARISON STUDY OF AUSTRALIAN AND INDONESIAN ENGLISH CURRICULUM FOR UPPER PRIMARY SCHOOL - Istiqomah, Faizatul (Lingua Scientia, 2013)
Abstract: In this article I would like to describe a short history of English curriculum in Indonesia followed by the explanation about the study which is about the curriculum and implementation of elementary schools in Indonesia to be compared to Australian curriculum. This study employs qualitative approach as the data are collected and analyzed in the form of words. The analysis of data is in the descriptive qualitative where the data are described and analyzed based on the research questions. The finding shows that there some similarities and differences in term of the teaching objectives, the learning activities, and the assessment.Â Keywords: Australian English curriculum, Indonesian English curriculum, primary schoolÂ Â